The properties of p-type nanostructured copper (I) iodide (CuI) thin films prepared by a novel Mister Atomizer Technique for Dye-Sensitized Solar Cell (DSSC) application: article - Yeop, Azilawati; Rusop, Mohamad (2012)
In this research, the nanostructured CuI thin film for the solid state dye-sensitized solar cells (SSDSSC) was produced by a spraying method which uses mister atomizer. The 0.05 mol of Cu solution was prepared at room temperature by mixing the Cul power with 50ml acetonitrile as solvent and doped with iodine. The Cul concentration was varied from 1 at % (atomic percent) until 5 at % of the iodine doping. Then the Cul thin films were deposited on a glass substrate. The electrical properties of CuI thin films were studied using current - voltage (1-V) solar simulator (CEP 2000) and the thickness of Cul thin films were measured using surface profile (VEECO DEKT AK 150). Then metal contacts have been deposited using sputter coater (EMITECH K550X). The best conductivity of the Cul thin film is at 4at% which is 6.94 x 10-1 S.cm in dark and 6.98 x 10-1 S.cm in illumination since it has less resistivity. The optical properties of Cul thin films were investigated by JASCO UVVIS/NIR spectrophotometer. The result of the transmittance spectra is at high transparency which is at 71 % - 90% nm. Then the surface morphology of the Cul thin films were characterized using field-emission scanning electron microscope (FESEM). The FESEM images show the Cul thin films were in nanoparticle size. The particle size evaluated from FESEM was at 25nm to 90 nm range. The electrical properties, optical properties and surface morphology of Cul thin film could be affected by changing the atomic percent (at%) of the doping concentration of iodine.